(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
Background: General anaesthesia is used for breast cancer surgery. The downside of generalanaesthesia includes inadequate pain control and a high incidence of nausea and vomiting. Generalanaesthesia with intravenous dexmedetomidine or intercostal nerve block reduce the incidence ofpostoperative pain. Objective: To evaluate the effectiveness of intravenous dexmedetomidine compared to intercostal nerveblocks in patients undergoing simple mastectomy with axillary dissection under general anaesthesia.Methods:It was a single-blinded prospective randomized comparative study. This study was conductedat the Department of Anaesthesia, Analgesia and Intensive Care Medicine, Bangabandhu Sheikh MujibMedical University (BSMMU), Dhaka from March 2018 to March 2019. A total of 60 patients sufferingfrom breast cancer admitted in the Department of General Surgery of BSMMU Dhaka and scheduledfor simple mastectomy with axillary dissection, were enrolled in this study. Results: Age ,height andweight were almost identical between two groups. Duration of anaesthesia and surgery were almostsimilar between two groups. The mean heart rate, systolic blood pressure, diastolic blood pressure ,mean arterial pressure did not significantly fluctuate in subsequent baseline follow up and 15 minuteand at 160 minutes parameters were almost similar within two groups.Mean time to achieve adequateAldrete recovery score after extubation was almost similar between two groups. Postoperative sedationlevel was also similar between two groups. Majorty of the surgeon were satisfied about anaesthesiatechnique in both group A and group B. Mean time of rescue analgesic requirement in postoperativeperiod was satistically significant (p<0.05) between two group but it was clinically less significant(groupA= 112 minutes and groupB=141minutes. Conclusion: Intravenous dexmedetomidine may be an alternative to intercostal nerve blocks inpatients undergoing simple mastectomy with axillary dissection under general anaesthesia as itprovided stable intraoperative haemodynamics, reduced blood loss and analgesic requirement, smoothrecovery, postoperative sedation level and surgeon satisfaction as well as intercostal nerve blocks. JBSA 2021; 34 (2) : 24-35